Awareness of social business in social media in Malaysia / Siti Hafizah Daud and Khatijah Othman - Daud, Siti Hafizah; Othman, Khatijah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2019)
The social enterprise movement in Malaysia is gathering its momentum. An increasing number of social entrepreneurs are taking an interest in this field of activity. Indirectly, this scenario increases the awareness of its significance and, in a range of viewpoints, promotes the social business experience in Malaysia. This article is an explanatory study which indicates the awareness of social business in Malaysia. The literature review was conducted from library research and website sources. It is divided into three sections: (i) definitions of social business, (ii) operating models for social enterprise in Malaysia, and (iii) definitions of social media and its development, and the awareness of young people on social business in relationship with social media in general. The first section begins with various definitions and interpretations of the term ‘social enterprise’, while the second part provides an operating model for social enterprises that are active in Malaysia as well as in relation to the market and potential beneficiaries. The third part is a discussion on social media by looking at definitions and the development of social business in Malaysia in general. With this explanation, it is hoped that the awareness of using social media in social business can be highlighted in better perspectives.